Association between subclinical hypothyroidism and glycemic control in older adults in a medical center in Peru - Neyra-Rivera, Carlos D. (2024)
Objective. To determine whether there is an association between subclinical hypothyroidism and glycemic control in older adults who received care at the “Centro M´edico Naval” from 2010 to 2015. Methods. This retrospective analytical study analyzed a secondary database of the care of elderly in the study hospital. The sample was comprised of 1,385 older adults. To detect an association between variables, the Poisson regression with robust variance was used at a significance level of 95%. The analyses were carried out with the STATA 16 program. Results. Of the elderly 45.6% were between 71 and 80 years old; 58.4% were women and 43.8% had a normal body mass index. There was evidence of inadequate glycemic control in 8.1% and subclinical hypo-thyroidism in 15.2% of the elderly patients. Subclinical hypothyroidism was more frequent in the inadequate glycemic control vs. adequate glycemic control populations (41.1% vs. 13.0%). In the multivariance analysis, subclinical hypothyroidism (aPR = 2.2295% CI [1.47–3.36]) was independent factor associated with inadequate glycemic control (p < 0.001). Conclusions. A significant association was detected between subclinical hypothyroidism and inadequate glycemic control in older adults who presented at the “Centro M´edico Naval” from 2010 to 2015.